Analysis of Contributing Factors to Stunting in Poso Regency: A Perspective from the Special Stunting Handling Index - Nurfatimah Nurfatimah; Sumiaty Sumiaty; Kadar Ramadhan; Taqwin Taqwin; I Putu Suiraoka (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Introduction: The prevalence of stunting in children in Indonesia, including Poso Regency, remains relatively high despite a decrease in recent years. This study aims to analyze factors associated with stunting in Poso Regency. Methods: This study employed a cross-sectional analytical method with a sample size of 250 mothers and their children under 2 years old, using structured questionnaires and direct measurements to collect data. Univariate analysis, chi-square tests and binary logistic regression were performed with a final report of adjusted odds ratios (AORs) and 95% confidence intervals (CI). All of the analyses used Stata version 15. Results: Results indicate a significant association between stunting and the child's gender, maternal education, immunization, and breastfeeding. Boys face a 2.3 times higher risk of stunting, while children of mothers with primary education have a 4.7 times higher risk compared to those with higher education. Non-immunized and non-breastfed children also exhibit significantly higher stunting risks. Conclusion: The study underscores the impact of factors such as the child's sex, maternal education, immunization, and breastfeeding on stunting in Poso Regency. The study emphasizes the need for targeted educational programs by healthcare professionals, policy-driven nutritional support initiatives, and community-based awareness campaigns to effectively address stunting in Poso Regency.